Business Intelligence Model for Decision-Making in a Gastronomic Sector MyPE (LACCEI, 2024)
The objective of the research was to design a business intelligence model for decision making in a SME of the gastronomic sector. The study has a qualitative, applied, prospective, cross-sectional, observational and non-experimental approach. The population consisted of 2000 clients and a sample of 50 clients determined by convenience. A survey was validated by expert judgment with a reliability of 0.86 Cronbach's alpha.For the situational diagnosis of the SME, the MEFE and MEFI matrices, Porter's 5 forces, PESTEL, MPC AMOFHIT and value chain were used. The requirements of the model were determined for the design of the database that allows the construction of the Data Mart and ETL. The estimated investment for the implementation of the model is S/.1 9065, taking into account personnel, equipment, materials, software and services costs. Finally, it was determined that the SME would save 45% by generating reports and increase its sales by 55%, in order to minimize service and production times and improve customer satisfaction by 100%.